Strengthening of Legal Understanding and Managerial Capacity Village Owned Enterprise Manager in Karo District - Detania Sukarja; Tri Murti Lubis; Syafrizal Helmi Situmorang; Keulana Erwin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The rapid development of technology has resulted in significant changes to the loan process, whichhas certainly made it easier for people who need to take loans so that they no longer need to go to banks or other financial service institutions. However,online loans can also cause problems if they are not well understood.In order to understand Peer to Peer Lending (onlineloans) in Indonesia,we need to refer to Financial Services Authority Regulation No.11/POJK.In this regulation, peer to peer lending (online loans) is defined as an act of providinglending and borrowing services directly between lenders and information technology-based loan recipients.As of August 14th, 2020, there are 157 fintech companies already registered and licensed in the Financial Services Authority (OJK). OJK urges the public to use registered and licensed fintech lending services. To increase public awareness and knowledge in peer to peer lending (online loans), we conducted a socialization in the form of counseling to peoplein Sunggal Village, Medan Sunggal. The method used in this socialization is a focus discussion, starting with a lecture session then continued with a Q&A session among participants. The lecture session was conducted in order to deliver important learning materials for the participant to know and understand. Meanwhile, the Q&A session was conducted in order to complete unclear material and help to solve the problems related to Online Peer to Peer Lending. After participating in this socialization, the public can identify trusted online loan providers, which are providers registered with the Financial Services Authority (OJK). This means people can be spared from untrusted online loan providers and can report them to OJK when they found unregistered providers with bad intentions.